Compact Bio-Fuel Burner - Mohamad Shaiful Ashrul, Ishak (Malaysian Association of Research Scientists (MARS), 2010)
Mohamad Shaiful Ashrul Ishak and his team won gold at Malaysia Technology Expo (MTE) 2007, 29th - 31st Mac 2007 at Putra World Trade Centre (PWTC), Kuala Lumpur. MTE 2007 organized by MARS and PROTEMP Exhibition.